Double Domination and Regular Domination in Intuitionistic Fuzzy Hypergraph - P. Aruna Sri; N. Thamaraikannan; K. Loganathan; Dinesh Kumar Chaudhary (Journal of Mathematics)
This study investigates the domination, double domination, and regular domination in intuitionistic fuzzy hypergraph (IFHG), which has enormous application in computer science, networking, chemical, and biological engineering. Few properties of double domination and regular domination of IFHG are established. Furthermore, the definitions of complement and independent set of IFHG are given. The relation between the domination of an IFHG and the independent set of its complement was discussed. Moreover, the application of the double domination in the IFHG was illustrated by determining the containment zones for epidemic situations like COVID-19.